A research-informed, school-based professional development workshop programme to promote dialogic teaching with interactive technologies. Issue 2 (15th March 2018) - Hennessy, Sara; Dragovic, Tatjana; Warwick, Paul
Abstract: The study reported in this article investigated the influence of a research-informed, school-based, professional development workshop programme on the quality of classroom dialogue using the interactive whiteboard (IWB). The programme aimed to develop a dialogic approach to teaching and learning mediated through more interactive uses of the IWB, through a model of active participation of students, collaborative knowledge-building, learning through inquiry and evaluating ideas. Ten professional development workshops based on video-stimulated discussions of practices were co-developed and conducted with an 'ambassador' within each of five school clusters. In total, 80 teachers from 15 schools, ranging from infant to secondary schools, participated. Data were collected through surveys, semi-structured interviews with teachers and ambassadors, teachers' posters created during workshop activities, lesson observations and a portfolio of dialogic classroom practices, mediated by the IWB. Findings strongly support the potential of this ambassador-led workshop model to involve teachers in developing their understandings of classroom dialogue and devising new approaches to support it. The research additionally confirms the potential of the IWB as a tool to support dialogic teaching.